Speech reception threshold benefits in cochlear implant users with an adaptive beamformer in real life situations. (March 2015) - Geißler, Gunnar; Arweiler, Iris; Hehrmann, Phillipp; Lenarz, Thomas; Hamacher, Volkmar; Büchner, Andreas
Abstract : Objectives: To compare the Naida CI UltraZoom adaptive beamformer and T-Mic settings in a real life environment. Methods: Speech reception thresholds (SRTs) were measured in a moderately reverberant room, using the German Oldenburger sentence test. The speech signal was always presented from the front loudspeaker at 0° azimuth and fixed masking noise was presented either simultaneously from all eight loudspeakers around the subject at 0°, ±45°, ±90°, ±135°, and 180° azimuth or from five loudspeakers positioned at ±70°, ±135°, and 180° azimuth. In the third test setup, an additional roving noise was added to the six loudspeaker arrangement. Results: There was a significant difference in mean SRTs between the Naida CI T-Mic and UltraZoom in each of the three test setups. The largest improvements were seen in the six speaker roving and fixed noise conditions. Adding ClearVoice to the Naida CI T-Mic setting significantly improved the SRT in both fixed noise conditions, but not in the roving noise condition. In each setup, the lowest SRTs were obtained with the UltraZoom plus ClearVoice setting. Discussion: The degree of improvement was consistent with previous beamforming studies. In the most challenging listening situation, with noise from eight speakers and speech and noise presented coincidentally from the front, UltraZoom still provided a significant benefit. When a moving noise source was added, the improvement in SRT provided by UltraZoom was maintained. Conclusion: When tested in challenging and realistic noise environments, the Naida CI UltraZoom adaptive beamformer resulted in significantly lower mean SRTs than when the T-Mic alone was used.